Additive Manufacturing of Titanium Alloys for Orthopedic Applications: A Materials Science Viewpoint. Issue 9 (28th May 2018) - Majumdar, Trina; Eisenstein, Neil; Frith, Jess E.; Cox, Sophie C.; Birbilis, Nick
Abstract : Titanium‐based orthopedic implants are increasingly being fabricated using additive manufacturing (AM) processes such as selective laser melting (SLM), direct laser deposition (DLD), and electron beam melting (EBM). These techniques have the potential to not only produce implants with properties comparable to conventionally manufactured implants, but also improve on standard implant models. These models can be customized for individual patients using medical data, and design features, such as latticing, hierarchical scaffolds, or features to complement patient anatomy, can be added using AM to produce highly functional patient‐anatomy‐specific implants. Alloying prospects made possible through AM allow for the production of Ti‐based parts with compositions designed to reduce modulus and stress shielding while improving bone fixation and formation. The design‐to‐process lead time can be drastically shortened using AM and associated post‐processing, making possible the production of tailored implants for individual patients. This review examines the process and product characteristics of the three major metallic AM techniques and assesses the potential for these in the increased global uptake of AM in orthopedic implant fabrication. Abstract : The use of additive manufacturing for the low‐cost, fast lead‐time manufacturing of customized orthopedic implants is becoming rapidly more feasible. The three major techniques used are selective laser melting (SLM), electron beam melting (EBM), and direct laser deposition (DLD). This review presents a timely examination of the current state of the art in each of these techniques, with a focus on the implant properties achievable by each technique. The issues that must be considered prior to and following fabrication are summarized, and the review ends with a consideration of the bench to bedside perspectives.